The Influence of Current Ratio, Total Debt to Total Assets, Total Assets Turn Over, and Return on Assets on Earnings Persistence in Automotive Companies - Adibah Yahya; Saepul Hidayat (Universitas Padjadjaran, 2020)
The purpose of this study is to determine the effect of the variable Current Ratio, Total Debt to Total Assets, Total Assets Turnover, Return on Assets, on earnings persistence. This study used secondary data, namely the annual financial statements of automotive companies listed on the Indonesia Stock Exchange from 2014-2018. The sample selection used a purposive sampling method. The data source is the financial ratios of automotive companies listed on the IDX. Methods of data analysis used the classic assumption test, multiple linear regression, T-test, F-test, and the coefficient of determination. The results showed that partial earnings persistence expressed in financial ratios consisting of the Return on Assets (ROA) significantly affect earnings persistence, while the Current Ratio (CR), Total Debt To Total Asset (TDTA) and Total Asset variables and Total Assets Turnover (TATO) has no significant effect on earnings persistence. Results of the simultaneous test, financial ratios consisting of CR, TDTA, TATO, and ROA had no significant effect on earnings persistence. R Square value of 0.076 can be interpreted that CR, TDTA, TATO, and ROA of 7.6% while the remaining 82.4% is influenced by other variables not examined